prove tthe following
Attachments:
![](https://hi-static.z-dn.net/files/df8/7b8fe6f0842b38187ad4d34759a0e61f.jpg)
Answers
Answered by
0
Step-by-step explanation:
1+cosA+sinA/1+cosA-sinA
devide cosA in both numerator & denominator
=secA+1+tanA/secA+1-tanA
=(secA+tanA)+(sec²A-tan²A)/ secA-tanA+1
=(secA+tanA)+(secA+tanA)(secA-tanA)/ (secA-tanA+1)
=(secA+tanA)(1+secA+tanA)/ secA-tanA+1
=secA+tanA
=1/cosA+sinA/cosA
=1+sinA/cosA
Answered by
1
Answer:
rqnpijcnj lzkn lkxnj lknjxc189uhoioyyyyyyyyyyyyyyyyyyyyyyyyyffgu45hndhud8eh7eh=-=-fny-=-wxhs9yUSXHUAXUSAHU=-=
Similar questions